Applying TRIZ to design and develop roof shield for two-wheeled motorcycle - Hoh, R. B.; Nasrul Azuan, Alang; Nasrul Hadi, Johari; Norhaida, Ab Razak; Juliawati, Alias (Penerbit UMP, 2023)
Online purchasing and food delivery have shown an increase in demand during the pandemic COVID-19. In Malaysia, the most preferred mode of transportation for food delivery is motorcycle. However, the hot weather and rain affect the delivery time. This paper presents the effort to design and develop a roof shield for a motorcycle to tackle the problem of delivery during uncertain weather conditions. A survey was conducted around Pekan and Kuantan, Pahang districts, encompassing a total of 100 respondents, including riders and customers. From respondents’ feedback, the design requirements for the roof shield were derived. Two conceptual designs were sketched based on the TRIZ approach and evaluated using the scoring test matrix. The roof shield is designed so that it is height adjustable and expandable to fit different brands of motorcycles, which have slightly different dimensions. Furthermore, the rotatable roof is developed to improve riding, especially during cornering. The fabricated roof was assembled on the AVETA DY90 and DEMAK EX90 motorcycles. Twenty random riders were chosen to test the roofed motorcycle on the road. The feedback collected from them showed overall satisfaction with the roof shield installed on the motorcycle. They believed that the roof can protect them from the sun’s rays and light rain thereby increasing delivery performance. The suggestion by the rider to further improve the roof is being considered for future design.